2019
DOI: 10.1002/jts.22465
|View full text |Cite
|
Sign up to set email alerts
|

Body‐ and Movement‐Oriented Interventions for Posttraumatic Stress Disorder: A Systematic Review and Meta‐Analysis

Abstract: To assess the efficacy of body-and movement-oriented interventions (BMOIs) in traumatized adults with posttraumatic stress disorder (PTSD), we conducted a systematic review and meta-analysis of pertinent literature. Four bibliographical databases (PsycINFO, Ovid MEDLINE(R), EMBASE, and the Cochrane Central Register of Controlled Trials) were searched using keywords and text words for trials on BMOIs addressing PTSD. The search included articles published between October 2005 and August 2017. Studies were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…In line with our previous study (Van de Kamp et al, 2019), we applied the following eligibility criteria for the meta-analysis: articles had to (a) be published in English, German, Dutch, or French; (b) have an abstract published in English; (c) be published in a peer reviewed journal; (d) include adult participants (i.e., 18 years of age and older) with a primary diagnosis of PTSD, per criteria in the fourth or fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM; i.e., DSM-IV or DSM-5); (e) include BMOI therapy, as defined and described by Emck and Scheffers (2019) as one of the investigated therapies; (f) be designed as a comparative outcome trial with a control group; and (g) involve a standardized, psychometrically evaluated outcome measure for PTSD. We used the same search strategy as the original study (see Supplementary Materials) and searched the same databases for articles published from November 2017 (i.e., the last search date in the previous study); reference lists of the included articles were also checked.…”
Section: Methods Eligibility Criteria Information Sources and Search ...supporting
confidence: 93%
See 1 more Smart Citation
“…In line with our previous study (Van de Kamp et al, 2019), we applied the following eligibility criteria for the meta-analysis: articles had to (a) be published in English, German, Dutch, or French; (b) have an abstract published in English; (c) be published in a peer reviewed journal; (d) include adult participants (i.e., 18 years of age and older) with a primary diagnosis of PTSD, per criteria in the fourth or fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM; i.e., DSM-IV or DSM-5); (e) include BMOI therapy, as defined and described by Emck and Scheffers (2019) as one of the investigated therapies; (f) be designed as a comparative outcome trial with a control group; and (g) involve a standardized, psychometrically evaluated outcome measure for PTSD. We used the same search strategy as the original study (see Supplementary Materials) and searched the same databases for articles published from November 2017 (i.e., the last search date in the previous study); reference lists of the included articles were also checked.…”
Section: Methods Eligibility Criteria Information Sources and Search ...supporting
confidence: 93%
“…Concordant with our original study (Van de Kamp et al, 2019), we expected to find a heterogeneous group of studies with regard to intervention types, participants, study methodology, and control conditions, resulting in high statistical heterogeneity of the effect sizes. Given the increase in available evidence, we deemed it worthwhile to reassess the variation and heterogeneity with subgroup analyses.…”
mentioning
confidence: 70%
“…BPT particularly considers the therapeutic alliance, which is also acknowledged as recruiting the social engagement system (Porges, 2021), as one of the key elements of the healing process (Rosendahl et al, 2021). A recent meta-analysis confirmed that BPT is beneficial for a wide spectrum of psychic disorders (Rosendahl et al, 2021), including PTSD (van de Kamp et al, 2019). between different body parts and the central nervous system (Cameron, 2001;Craig, 2002;Gellhorn, 1964;Mandler et al, 1958;Mehling et al, 2009;Sherrington, 1906).…”
Section: Bpt: What Is It and How Is It Related To The Regulation Of T...mentioning
confidence: 99%
“…Mindfulnessbased approaches have also become popular for trauma treatment which are based on Eastern philosophy and the practice of mindfulness-based meditation (Briere & Scott, 2006;Kabat Zinn, 1990, 2003Siegel, 2010). Body-based approaches, such as somatic experiencing and sensory-motor therapy, as well as the creative arts therapies, such as art therapy, music therapy, drama therapy, dance therapy, poetry therapy, and psychodrama, have become increasingly utilized in trauma treatment in recent times (Dayton, 2015;Foa, Keane, Friedman, & Cohen, 2008;Gene-Cos, Fisher, Ogden, & Cantrell, 2016;Giacomucci, 2018;Giacomucci & Marquit, 2020;Hudgins & Toscani, 2013;Johnson & Sajnani, 2014;Levine, 2010;Schouten et al, 2015;van de Kamp et al, 2019;van der Kolk, 2014). In addition to the aforementioned methods, many providers or programs utilize an eclectic approach which integrates multiple of the modalities above (SAMHSA, 2014b).…”
Section: Trauma-informed Practice Versus Trauma-focused Practicementioning
confidence: 99%